2023
DOI: 10.1038/s41598-023-36370-3
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA sequencing analysis of peptide-affinity isolated plasma extracellular vesicles distinguishes pancreatic cancer patients from non-affected individuals

Abstract: Pancreatic ductal adenocarcinoma (PDAC) has a high fatality rate, mainly due to its asymptomatic nature until late-stage disease and therefore delayed diagnosis that leads to a lack of timely treatment intervention. Consequently, there is a significant need for better methods to screen populations that are at high risk of developing PDAC. Such advances would result in earlier diagnosis, more treatment options, and ultimately better outcomes for patients. Several recent studies have applied the concept of liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…We observed that miR-18a and miR-106a in plasma small extracellular vesicles (EVs) were significantly elevated in early-stage PDAC patients compared to healthy controls. This finding aligns with other studies, suggesting these miRNAs as reliable indicators for early PDAC detection [ 3 , 9 , 18 - 20 ]. The consistency across different research efforts reinforces the potential of these miRNAs as non-invasive biomarkers.…”
Section: Reviewsupporting
confidence: 93%
“…We observed that miR-18a and miR-106a in plasma small extracellular vesicles (EVs) were significantly elevated in early-stage PDAC patients compared to healthy controls. This finding aligns with other studies, suggesting these miRNAs as reliable indicators for early PDAC detection [ 3 , 9 , 18 - 20 ]. The consistency across different research efforts reinforces the potential of these miRNAs as non-invasive biomarkers.…”
Section: Reviewsupporting
confidence: 93%
“…EVs from the sample of PC patients and healthy controls and assessed specific miRNA-derived EV content using reverse transcription polymerase chain reaction (RT-PCR) and miRNA-specialised sensors to determine if EVs can be used as diagnostic tool ( 37 - 42 ). MiR-550, miR-21 miR-17-5p and miR-10b expression was found to be elevated in PC patients, implying that they can serve as potential markers for PC detection ( 41 , 43 - 46 ). Madhavan et al examined blood EVs for five PC-initiating cell markers and four combination miRNAs ( 47 ).…”
Section: Role Of Evs As Potential Pc Biomarkersmentioning
confidence: 98%
“…The Vn96 peptide is a peptide a nity capture method developed for the capture of EVs in clinically relevant bio uids [18-20, 33, 38-41]. Numerous studies have shown captured Vn96-EVs from plasma contain canonical EV markers, and Vn96 has been utilized for the discovery of EV cargobiomarkers in amyotrophic lateral sclerosis [39] and cancers, such as prostate [42], lung [43], and pancreatic ductal adenocarcinoma [44].…”
mentioning
confidence: 99%